Propofol plus low-dose dexmedetomidine infusion and postoperative delirium in older patients undergoing cardiac surgery - Momeni, Mona; Khalifa, Céline; Lemaire, Guillaume; Watremez, Christine; Tircoveanu, Robert; Van Dyck, Michel; Kahn, David; Rosal Martins, Maria; Mastrobuoni, Stefano; De Kerchove, Laurent; Zango, Serge Henri; Jacquet, Luc-Marie (British journal of anaesthesia : BJA, 2021)
Postoperative delirium (POD) is a frequent complication in older patients. Dexmedetomidine might be effective in decreasing the incidence of POD. We hypothesised that adding low-dose rate dexmedetomidine infusion to a propofol sedation regimen would have fewer side-effects and would counteract the possible delirium producing properties of propofol, resulting in a lower risk of POD than propofol with placebo. In this double-blind placebo-controlled trial, patients ≥60 yr old undergoing on-pump cardiac surgery were randomised 1:1 to the following postoperative sedative regimens: a propofol infusion and dexmedetomidine (0.4 μg kg−1 h−1) or a propofol infusion and saline 0.9% (placebo group). The study drug was started at chest closure and continued for 10 h. The primary endpoint was in-hospital POD, assessed using the Confusion Assessment Method and chart review method. POD over the course of hospital stay occurred in 31/177 (18%) and 33/172 (19%) patients in the dexmedetomidine and placebo arm, respectively (P=0.687; odds ratio=0.89; 95% confidence interval, 0.52–1.54). The incidence of POD in the intensive care alone, or on the ward alone, was also not significantly different between the groups. Subjects in the dexmedetomidine group spent less median time in a delirious state (P=0.026). Median administered postoperative norepinephrine was significantly higher in the dexmedetomidine group (P<0.001). One patient in the dexmedetomidine group and 10 patients in the placebo group died in the hospital. Adding low-dose rate dexmedetomidine to a sedative regimen based on propofol did not result in a different risk of in-hospital delirium in older patients undergoing cardiac surgery. With a suggestion of both harm and benefit in secondary outcomes, supplementing postoperative propofol with dexmedetomidine cannot be recommended based on this study. NCT03388541.